The relevance of using accounting fundamentals in the Euronext 100 index - Daniel Navas, Raúl; Matias Gama, Ana Paula; Ricardo Bentes, Sónia (Review of Business Management, 2023)
Purpose – The purpose of this research is to investigate whether using an accounting fundamental strategy can provide valuable information about the value of a business and generate positive excess buy-and-hold returns on stocks in the Euronext 100 index. Theoretical framework – The theoretical framework of the study is based on the combination of valuation theory and accounting research. We rely on fundamental analysis as a stock valuation method, which involves looking at both quantitative and qualitative information in a company’s economic and financial records. Design/methodology/approach – We examine the relevance of growth and earnings response coefficients, as well as Piotroski’s F-scores and Lev and Thiagarajan’s L-scores in predicting future stock returns. The analysis covers the years 2000 to 2020. Findings – The study finds that accounting fundamental signals provide value-relevant information to investors and have a significant and positive relationship with future buy-and-hold market returns, resulting in high-scoring portfolios achieving significant average annual market excess returns. Practical & social implications of research – The results of the study have practical implications for investors who use fundamental analysis as an investment strategy. The results indicate that accounting fundamentals provide value-relevant information to investors and can lead to positive excess buy-and-hold returns. Originality/value – The study contributes to the understanding of the role of fundamentals in firm valuation and provides fresh insights into binary models and fundamental analysis applied to European markets. In addition, the study tests the robustness of fundamental strategies using fixed effects regression analysis. Keywords: European capital markets, accounting fundamentals, stock returns, portfolio formation, Euronext 100 index.